The role of open university and its impact on the development of a skilled health workforce - Raziana Che Aziz; Nurhan Norris Ma Weng Chuen; Rosnida Abu Bakar; Sivabalan Rajagopal (2022)
The Covid-19 pandemic and the emergence of its various strains, most recently Omicron, have provided us with an opportunity to observe how the healthcare environment has changed and how health care workers (HCWs) have responded to these changes. The healthcare sector is evolving faster than ever, making it essential for HCWs to receive top-notch, ongoing training and education. Making sure patients receive the finest treatment is a responsibility shared by HCWs. HCWs can ensure this by taking part in regular training during their career. However, the announcement of the movement control order (MCO) by the National Security Council has indefinitely disrupted the learning and teaching in tertiary centres and the majority were forced to suspend their learning activities. This study investigates the role and positive impact of Open University on developing a skilled health workforce in the post-pandemic era, leveraging on industry 4.0. METHOD. A multi-centric cross-sectional survey-based study was conducted to explore the perception among students of nursing and Assistant Medical Officer at Open University Malaysia. RESULTS. This paper aims to explore the role and the subsequent impact of Open University Malaysia on the development of a skilled healthcare workforce. CONCLUSION. The open distance learning model should be considered to change the landscape of conventional medical and nursing education to allow more opportunities for already busy nurses and Assistant Medical Officers to further their tertiary education to become the most qualified individuals to meet the growing need of our local healthcare industry. (Abstract by authors)